Assimilation of National and Business Strategic Management as Response to Globalisation Challenges - Bosas, Antanas (Ekonomika, 2002)
The present article deals with implementation of strategic management methods at national and organisational level. The change of view towards the essential understanding of strategic management is being shown. A great emphasis is given to the analysis of strategic management method implementation hindrances viewing it as an effective response to globalisation challenges. Explanation of fundamental reorientation of organisational architectonics for solution of the operative to strategic problems is given. The basic management consultancy function with a goal of effective implementation of strategic man.gement both at national and organisational level is being grounded. In order to effectively oppose globalisation pressure it is essential to concentrate strategic management efforts for training competitive potential in all spheres of activity and business organisations.